Black Panther : the intergalactic empire of Wakanda. Part four - Coates, Ta-Nehisi (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2021)
"The final volume of Ta-Nehisi Coates' landmark run is the end of an era for the Black Panther! The groundbreaking story reaches a tipping point as the ruthless N'Jadaka comes for Earth! To protect our planet from N'Jadaka's violent invasion, the nation of Wakanda must go to war against its own future--and its first, best and only hope lies in the Panther! But where is he? Even the gods are beginning to despair--but Bast will not abandon her avatar, even if she has to recruit an outsider to save him!"--